Parents’ attitudes as mediators between knowledge and behaviours in unintentional injuries at home of children aged 0–3 in Shanghai, Eastern China: a cross-sectional study - Qi Zhang; Wei Deng; Xueqi Ma; Ruo Jiang; Huiping Wang; Fengshui Chang (BMJ Open)
Objective Parental behaviours are important in preventing unintentional injury at home among young children. Previous research showed an inconsistent relationship between knowledge and behaviours, indicating that the mechanisms may vary for different behaviours. This study aimed to examine the mediating roles of different attitudes in the mechanism of knowledge acting on different behaviours.Design Cross-sectional study.Setting Eastern China.Participants Participants were recruited using stratified community-based sampling. A total of 488 parents of children aged 0–3 years participated in the study and 476 (97.5%) valid questionnaires were recovered.Primary outcome measures Parents’ knowledge, attitudes (including injury attribution, preventability and responsibility) and behaviours (including supervision behaviours, risky behaviours and providing a safe home environment).Results The results of mediation analysis showed that the mediator variables were different for different behaviours and that all associations were positive. Parents’ knowledge (β 0.19, 95% CI 0.13 to 0.24) and attitude of injury attribution (β 0.37, 95% CI 0.21 to 0.46) were directly associated with risky behaviours. Attitude of preventability was directly associated with parents’ supervision behaviour (β 0.27, 95% CI 0.14 to 0.40). Parents’ attitude of preventability mediated the positive association between knowledge, attitudes of injury attribution and responsibility, and supervision behaviours, as well as providing a safe home environment. In addition, the occurrence of child injuries at home was directly associated with home environment (β −0.41, 95% CI −0.82 to −0.01).Conclusions The current findings confirm that attitudes play varying mediating roles between knowledge and different behaviours. An important recommendation is that parents’ attitudes, especially towards preventability and responsibility, need to be considered when health providers develop health education programmes targeted at improving parental supervision behaviours and providing a safe home environment.